Kegagalan Peacekeeping Operation PBB pada Konflik Republik Demokratik Kongo - Wakhidah Hasna Khairunnisa; Rr. Hermini Susiatiningsih (Journal of International Relations Diponegoro, 2019)
This research topic addresses the failure of MONUSCO to create peace in the Democratic Republic of the Congo. Creating peace is a mandate that must be carried out by MONUSCO. This topic is interesting because of the fact that peace in the Democratic Republic of the Congo has not occurred until now, while the UN peacekeeping operation has been running since 1998 and is one of the longest and spend a lot of funds missions in the history of peace operations. In Dennis C. Jett's theory of the failure of peacekeeping operations, there is a predeployment factor and the deployment factor. In terms of predeployment, decision making, mandate, quality and quality of peacekeeper are important. Meanwhile in deployment factor, there are internal and external factors that have equal influence on the peace process. Therefore, the hope of achieving peace cannot be achieved. Because choosing MONUSCO itself is one of the causes of the failure to create peace, it also makes the rebel groups and interference from the interested parties into other factors that cause problems.